Park-and-Ride Choice Behavior in a Multimodal Network with Overlapping Routes. Issue 3 (March 2020) - Webb, Alexander; Khani, Alireza
This study estimates a discrete choice model from on-board survey data for park-and-ride (PNR) user's station choice, and finds that users prefer a higher proportion of their trip time spent on transit than in a car. No evidence is found that users choose the PNR location that minimizes their overall travel time, but there is strong evidence that PNR locations closer to the direction of their destination are preferred. No significant relationship is found between PNR choice, user age, income, or gender. PNR facility amenities are found to be insignificant across all models tested, and the rail and bus rapid transit service provide a significant benefit to PNR user utility when compared to the express bus service. This study contributes to existing literature by accounting for route overlap among alternatives using a path size factor in the logit model estimation. A nested logit model for different transit types is estimated, but is surpassed in predictive ability by a multinomial and mixed logit model. Ultimately, the models are found to predict transit route choice more accurately than PNR location choice, improving on the PNR choice prediction by about 11%. Similarly, choice set alternatives that overlap with a user's observed route are found to generally have higher choice probabilities than non-overlapping alternatives.